1946
DOI: 10.1242/jeb.22.3-4.191
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Acid in the Digesta of Ruminants and Other Animals

Abstract: A mixture of volatile organic acids, consisting for the most part of the fatty acids, acetic, propionic and butyric, is a characteristic product offermentation within the alimentary tract. It was shown previously that volatile acids are absorbed directly from the organ in which they are produced (Barcroft, McAnally & Phillipson, 1944), and this fact, together with a consideration of the quantities present in the digesta—a subject with which the present paper is concerned—suggest that they form a valuable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1954
1954
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The SCFA content in the intestine was positively correlated with the number and activity of intestinal bacteria 35 . Short‐chain fatty acids mainly consist of acetate, propionate and butyrate, and they are the predominant metabolites produced by bacterial fermentation of complex carbohydrates in the hindgut of pigs 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCFA content in the intestine was positively correlated with the number and activity of intestinal bacteria 35 . Short‐chain fatty acids mainly consist of acetate, propionate and butyrate, and they are the predominant metabolites produced by bacterial fermentation of complex carbohydrates in the hindgut of pigs 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The SCFA content in the intestine was positively correlated with the number and activity of intestinal bacteria. 35 Short-chain fatty acids mainly consist of acetate, propionate and butyrate, and they are the predominant metabolites produced by bacterial fermentation of complex carbohydrates in the hindgut of pigs. 36 In vitro experiments showed that P, as a coenzyme component, is important for the bacterial degradation of dietary fiber, and the synthesis of bacterial cellulase depends on the supply level of P. 37,38 Phosphorus deficiency could result in reduced bacterial fermentation of cellulose, which in turn leads to decrease in SCFA production.…”
Section: Discussionmentioning
confidence: 99%
“…Early comparative studies demonstrated that short-chain fatty acid concentrations in the small intestine were small across both ruminant and nonruminant species [24]. Dietary lipid composition is altered by ruminal microbial populations via lipolysis and biohydrogenation [25], which alters duodenal digesta by increasing the concentration of non-esterified saturated fatty acids.…”
Section: Small Intestinal Digesta Composition and Passage Rate 21 Sma...mentioning
confidence: 99%
“…Nevertheless, the possibility of permeation of the omasal wall by these ions makes them unreliable as accurate markers of the absorption of water; and the further possibility that some of the reticular contents may bypass the omasum and flow directly to the abomasum via the omasal groove has rendered equivocal the use of markers for the assessment of the extent to which water is absorbed. It has been suggested (Elsden, Hitchcock, Marshall & Phillipson, 1946) that the greater part of the fatty acids in solution in the liquid portion of the material received from the reticulum are absorbed from the omasum, but here again the evidence is incomplete because of lack of knowledge of how liquids and solids are passed through the omasum. Fatty acids are undoubtedly absorbed there (Barcroft, McAnally & Phillipson, 1944), and the ratio of acids to solids is much reduced (Elsden et al 1946), yet if fluid were separated from the solids mechanically, rather than absorbed through the walls of the omasum, the absorption of fatty acid need not be as extensive as has been implied.…”
mentioning
confidence: 99%
“…It has been suggested (Elsden, Hitchcock, Marshall & Phillipson, 1946) that the greater part of the fatty acids in solution in the liquid portion of the material received from the reticulum are absorbed from the omasum, but here again the evidence is incomplete because of lack of knowledge of how liquids and solids are passed through the omasum. Fatty acids are undoubtedly absorbed there (Barcroft, McAnally & Phillipson, 1944), and the ratio of acids to solids is much reduced (Elsden et al 1946), yet if fluid were separated from the solids mechanically, rather than absorbed through the walls of the omasum, the absorption of fatty acid need not be as extensive as has been implied.…”
mentioning
confidence: 99%